Dynamics, Control, and Applications to Applied Engineering and Life - Balthazar, Jose M. [UNESP]; Goncalves, Paulo B.; Tusset, Angelo M.; Litak, Gregory (L and H Scientific Publishing, 2025)
This special issue contains 7 papers on Dynamics, Control and Ap- plications to Applied Engineering and Life Science. The aim of this Special Issue is to collate original research articles that focus on the re- cent theoretical, computational, and experimental results in the field of nonlinear dynamics focusing on different engineering applications
Keywords: Dynamics Control; Engineering dynamics; Life sciences